After that night - Slaughter, Karin 1971- (New York, NY William Morrow, an imprint of HarperCollins Publishers, 2023)
"After that night every thing changed... Fifteen years ago, Sara Linton's life changed forever when a celebratory night out ended in a violent attack that tore her world apart. Since then, Sara has remade her life. A successful doctor, engaged to a man she loves, she has finally managed to leave the past behind her. Until one evening, on call in the ER, everything changes. Sara battles to save a broken young woman who's been brutally attacked. But as the investigation progresses, led by GBI Special Agent Will Trent, it becomes clear that Dani Cooper's assault is uncannily linked to Sara's. And the past isn't going to stay buried forever..."--Dust jacket flap.
112164
Keywords: Trent, Will -- (Fictitious character) -- Fiction; Linton, Sara -- (Fictitious character) -- Fiction; Georgia. -- Bureau of Investigation -- Fiction; Government investigators -- Fiction; Medical examiners (Law) -- Fiction; Women -- Crimes against -- Fiction; Rape victims -- Fiction; Suspense fiction; Detective and mystery fiction; Fiction; Novels; Thrillers (Fiction)